Car-Parrinello molecular dynamics simulations of Na⁺–Cl⁻ ion pair in liquid water - Khalack, J.M.; Lyubartsev, A.P. (Condensed Matter Physics, 2004)
The aqueous solvation shell of a Na⁺–Cl⁻ pair is studied using Car-Parrinello
molecular dynamics simulations. Water-mediated and contact states
of the ion pair are investigated. The first hydration shell of the Na⁺ ion
is found to be octahedral with one vacant position for both states. In the
contact state one of the water molecules is substituted by the Cl⁻ ion.
The first hydration shell of the Cl⁻ is less structured and strongly effected
by the proximity of the Na⁺ in the contact state. The oxygen coordination
numbers for Na⁺ and Cl⁻ are 4.9 and 5.6 for the water-mediated state, and
3.6 and 6.4 for the contact state. The corresponding hydrogen coordination
numbers are 10.9 and 5.2; 9.2 and 3.9, respectively. Методами молекулярної динаміки Кара-Паррінелло вивчалася гідратна оболонка іонної пари Na⁺–Cl⁻. Досліджувалися медійований водою та контактний стан іонної пари. Знайдено, що перша гідратна оболонка іону Na⁺ є виражено октаедричною в обох станах. У контактному стані має місце заміщення однієї з молекул води іоном хлору. Перша гідратна оболонка іону Cl⁻ є менш структурованою й на неї сильніше впливає близькість іону натрію у контактній парі. Кисневі координаційні числа іонів натрію і хлору дорівнюють 4.9 та 5.6 для медійованого водою стану, та 3.6 і 6.4 для контактного стану іонної пари. Відповідні водневі координаційні числа становлять 10.9 і 5.2 та 9.2 і 3.9.